2017
DOI: 10.1111/anae.14040
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiac output response to colloid preload and vasopressor therapy during spinal anaesthesia for caesarean section in patients with severe pre‐eclampsia: a randomised, controlled trial

Abstract: SummaryWe examined the haemodynamic effects of colloid preload, and phenylephrine and ephedrine administered for spinal hypotension, during caesarean section in 42 women with severe early onset pre-eclampsia. Twenty patients with predelivery spinal hypotension were randomly allocated to receive an initial dose of either 50 lg phenylephrine or 7.5 mg ephedrine; the primary outcome was percentage change in cardiac index. After a 300-ml colloid preload, mean (SD) cardiac index increased from 4.9 (1.1) to 5.6 (1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
(28 reference statements)
0
15
0
2
Order By: Relevance
“…In a subsequent randomised trial investigating spinal anaesthesia for caesarean section in early onset severe pre‐eclampsia, the maternal haemodynamic effects of ephedrine and phenylephrine were formally compared. After a 300‐ml colloid pre‐load, a median bolus dose of 50 μg phenylephrine returned the spinal anaesthesia‐induced changes in systemic vascular resistance, heart rate and cardiac output towards baseline more effectively than 15 mg ephedrine boluses .…”
Section: Special Circumstancesmentioning
confidence: 95%
“…In a subsequent randomised trial investigating spinal anaesthesia for caesarean section in early onset severe pre‐eclampsia, the maternal haemodynamic effects of ephedrine and phenylephrine were formally compared. After a 300‐ml colloid pre‐load, a median bolus dose of 50 μg phenylephrine returned the spinal anaesthesia‐induced changes in systemic vascular resistance, heart rate and cardiac output towards baseline more effectively than 15 mg ephedrine boluses .…”
Section: Special Circumstancesmentioning
confidence: 95%
“…1) of which finally eight studies, including 712 parturients, were analysed. [18][19][20][21][22][23][24][25] Five studies reported on caesarean section for preeclamptic women and three studies on other high-risk cases. Details of the studies are shown in Table 1.…”
Section: Study Selection Study Characteristics and Risk Of Biasmentioning
confidence: 99%
“…Spinal anestezi sonrası oluşan hipotansiyonu önlemek için preload veya koload, sol tilt manevrası, profilaktik efedrin ya da diğer vazopresörlerin uygulandığı geleneksel yöntemlerin kendi aralarında karşılaştırılması ile ilgili çeşitli çalışmalar yapılmıştır (11)(12)(13)(14)(15)(16)(17) . Ancak PBK 'ya bağlı oluşan fizyolojik değişiklikleri ortaya koyan çok az çalışma vardır.…”
Section: Discussionunclassified